Nodal Pulay terms for accurate diffusion quantum Monte Carlo forces - Badinski,A; Haynes,PD; Needs,RJ (PHYS REV B, 2008)
Exact expressions are derived for forces within the mixed and pure fixed-node diffusion quantum Monte Carlo (DMC) methods. These expressions include the "nodal terms" which arise from the discontinuity in the gradient of the DMC wave function at the nodal surface. We devise a practical scheme for estimating the nodal terms, and demonstrate that their inclusion leads to very accurate forces.